Teaching Personal Initiative Beats Traditional Training in Boosting Small Business in West Africa - Campos, Francisco; Frese, Michael; Goldstein, Markus; Iacovone, Leonardo; Johnson, Hillary C.; McKenzie, David; Mensmann, Mona (American Association for the Advancement of Science, 2017)
Standard business training programs aim to boost the incomes of the millions of self-employed business owners in developing countries by teaching basic financial and marketing practices, yet the impacts of such programs are mixed. We tested whether a psychology-based personal initiative training approach, which teaches a proactive mindset and focuses on entrepreneurial behaviors, could have more success. A randomized controlled trial in Togo assigned microenterprise owners to a control group (n = 500), a leading business training program (n = 500), or a personal initiative training program (n = 500). Four follow-up surveys tracked outcomes for firms over 2 years and showed that personal initiative training increased firm profits by 30%, compared with a statistically insignificant 11% for traditional training. The training is cost-effective, paying for itself within 1 year. This is the author's version of the work. It is posted here by permission of the AAAS for personal use, not for redistribution. The definitive version was published in Science Vol 357, issue 6357: 1287-90.